Multi-strip silicon sensors for beam array monitoring in micro-beam radiation therapy. Issue 12 (December 2016) - Alagoz, E.; Brauer-Krisch, E.; Bravin, A.; Cornelius, I.; Fournier, P.; Hansen, T.E.; Kok, A.; Lerch, M.; Monakhov, E.; Morse, J.; Pacifico, N.; Petasecca, M.; et al.
Highlights: We have developed silicon sensors for online beam monitoring of MRT beams. The sensors have been tested in sessions at the ID17 and ID21 beamline. The sensors behave as per design specifications. The sensors are radiation hard, showing no signs of damage up to doses of 250 MRad. The electrode configuration correctly isolates the regions of interest, preventing cross-talk between the different strips. Abstract: We present here the latest results from tests performed at the ESRF ID17 and ID21 beamlines for the characterization of novel beam monitors for Microbeam Radiation Therapy (MRT), which is currently being implemented at ID17. MRT aims at treating solid tumors by exploiting an array of evenly spaced microbeams, having an energy spectrum distributed between 27 and 600 keV and peaking at 100 keV. Given the high instantaneous dose delivered (up to 20 kGy/s), the position and the intensity of the microbeams has to be precisely and instantly monitored. For this purpose, we developed dedicated silicon microstrip beam monitors. We have successfully characterized them, both with a microbeam array at ID17, and a submicron scanning beam at ID21. We present here the latest results obtained in recent tests along with an outlook on future developments.